A medieval patchwork song: poetry, prayer and music in a thirteenth-century conductus. Issue 2 (14th October 2016) - CALDWELL, MARY CHANNEN
ABSTRACT: Eight times a day, the prayer Deus in adiutorium meum intende sounded from the lips of the faithful as the standard introduction to the Office Hours. Infiltrating daily life through the liturgy and popular interjections, the psalm verse Deus in adiutorium served a devotional function marked by versatility and popularity. Yet, despite its omnipresence, as well as its inherently vocalic identity, the verse was only rarely troped musically or poetically. A collection of thirteenth-century monophonic and polyphonic tropes of the verse circulating in France in motet collections and festive offices represents one of the few moments of heightened musical interest in the prayer. This article draws attention, for the first time, to the musical and textual connection between these tropes and Pater creator omnium, a thirteenth-century refrain song. This monophonic song from France also belongs firmly to the medieval cento genre, with both its musical and textual construction based on the piecing together of borrowed text and music – including Deus in adiutorium . This article argues that Pater creator omnium stands at the intersection of two important yet understudied histories: the musical and textual troping of Deus in adiutorium and the medieval cento. Analysis of this song ultimately illustrates the creative processes behind the making of a pre-modern song.